Numerical Simulation of Scour Process Around Offshore Wind Turbine Monopile Foundation in Steady Flow - Bing XIA; Desheng MIAO; Min ZHANG; Huaixi LIU; Wenpeng GE (南方能源建设, 2023)
[Introduction] Scouring around pile foundation is an important technical problem in the construction and maintenance of offshore wind power plants. The scour hole developed under the environmental load like wave, current, etc. would reduce the stability of pile-soil structure and cause a non-negligible impact on the safety of the whole structure. [Method] In this paper, CFD technique combined with sand transport model were employed, scour around cylinder pile in sandy seabed under steady current was numerically simulated and studied by solving the nonlinear coupling equations of flow and scour, the development process of scour hole around pile was observed, and the time-varying curve of scour depth was obtained. [Result] The computing results show that the scour depth increases rapidly at the beginning of scouring, and then the process slows down gradually. In the calculation time of 16 minutes, the scour depth grows to 0.81 times the pile diameter. [Conclusion] According to the development of scour depth, it is suggested that for the wind farm located in sandy seabed aera, scour protection should be considered during the construction period, and the methods such as increasing the protective structures are recommended to prevent scour forming and extending.